Value of integrated pulmonary index monitoring for the detection of adverse respiratory events in patients undergoing sedation for gastrointestinal system endoscopy - Kefeli Celik, Hale; Doganay, Zahide; Askin, Atakan (Journal of the Pakistan Medical Association, 2024)
Objective: To determine if the integrated pulmonary index detects changes in ventilation status early in patients undergoing gastrointestinal endoscopy under sedation, and to determine the risk factors affecting hypoxia. Method: The retrospective study was conducted at the endoscopy unit of a tertiary university hospital in Turkey and comprised data between October 2018 and December 2019 related to patients of either gender aged >18 years who were assessed as American Society of Anaesthesiologists grade I-III and underwent elective lower and upper gastrointestinal endoscopy. Monitoring was done with capnography in addition to standard procedures. Data was analysed using SPSS 23. Results: Of the 154 patients, 94(%) were females and 60(%) were males. Th overall mean age was 50.88±11.8 years (range: 20-70 years). Mean time under anaesthesia was 23.58±4.91 minutes and mean endoscopy time was 21.73±5.06 minutes. During the procedure, hypoxia was observed in 42(27.3%) patients, severe hypoxia in 23(14.9%) and apnoea in 70(45.5%). Mean time between apnoea and hypoxia was 12.59±7.99 seconds, between apnoea and serious hypoxia 21.07±17.64 seconds, between integrated pulmonary index score 1 and hypoxia 12.91±8.17 sec, between integrated pulmonary index score 1 and serious hypoxia 21.59±14.13 seconds, between integrated pulmonary index score <7 and hypoxia 19.63±8.89 seconds, between integrated pulmonary index score <7 and serious hypoxia 28.39±12.66 seconds, between end-tidal carbon dioxide and hypoxia 12.95±8.33 seconds, and between end-tidal carbon dioxide and serious hypoxia 21.29±7.55 seconds. With integrated pulmonary index score 1, sensitivity value for predicting hypoxia and severe hypoxia was 88.1% and 95.7%, respectively, and specificity was 67% and 60.3%, respectively. With integrated pulmonary index score <7, the corresponding values were 100%, 100%, 42% and 64.1%, respectively. Conclusion: Capnographic monitoring, especially the follow-up integrated pulmonary index score, was found to be valuable and reliable in terms of finding both time and accuracy of the risk factor in the diagnosis of respiratory events. Key Words: Endoscopy, Hypoxia, Index monitoring, Pulmonary.